3 idiotas [videorecording (DVD)] : = 3 idiots - Bolado, Carlos; Higareda, Martha, 1983-; Higareda, Martha, 1983-; Dosal, Alfonso; Vázquez, Christian (Pantelion : Lionsgate, 2017)
Two friends set out on a journey to find their long-lost buddy with whom they shared a lot of unforgettable adventures in college.